English Teachers’ Perception of Project-Based Learning in Teaching English (A Case Study at SMPN 1 Jonggat) - Rampes, Sovia Lavender; Arafiq; Wardana, Lalu Ali (Journal of English Education Forum (JEEF), 2024)
In the era of global competition, enhancing English language skills is critical, and project-based learning (PjBL) presents a potential model to improve student engagement and language competence. This qualitative case study, conducted at SMPN 1 Jonggat in Central Lombok, Nusa Tenggara Barat, examines English teachers' perceptions of PjBL, focusing on its effectiveness, challenges, and implementation strategies. Using a purposive sample of three English teachers who employ PjBL in their classrooms, data were collected through semi-structured interviews and close-ended questionnaires to capture detailed insights into teachers' attitudes and experiences with PjBL. Semi-structured interviews allowed for in-depth exploration of teachers' subjective experiences, while questionnaires provided structured data on specific aspects of PjBL’s implementation. Data were analyzed following Miles and Huberman's three-step process—data reduction, data display, and conclusion drawing/verification—to systematically interpret findings. This study contributes valuable insights for educators seeking to enhance English language teaching through PjBL, offering a framework for understanding both the benefits and challenges of PjBL from teachers’ perspectives in a secondary school context. Findings are expected to support improved teaching strategies and contribute to more effective English education practices.